Dominasi Patriarki Terhadap Tokoh Perempuan dalam Novel Gadis Pantai: Kajian Kritik Sastra Feminis - Tanjung, Tia Wulandari; Hayati, Yenni (GERAM (Gerakan Aktif Menulis), 2025)
This study examines gender inequality in Pramoedya Ananta Toer's novel Gadis Pantai (The Beach Girl) using a feminist approach, focusing on the portrayal of patriarchal domination and its impact on the female character, Gadis Pantai. The gap seen in related literature often overlooks the importance of studying gender inequality in Indonesian literature, especially in terms of the influence of social structures on women's lives. This study aims to identify and analyse the forms of gender inequality experienced by Gadis Pantai, including subordination, marginalisation, stereotyping, double burden, and violence. Using a qualitative approach and literary text analysis, this study finds that the gender inequality depicted in this novel is highly relevant to the issues of gender inequality that still exist in contemporary society. The main findings show that although Gadis Pantai struggles to gain autonomy and freedom, she remains trapped in a role determined by a patriarchal system that limits her potential. This study affirms that Gadis Pantai is not only a literary work that reflects social injustice in the past, but also serves as a relevant social critique for fighting for gender equality in modern society.